2011
DOI: 10.1159/000328992
|View full text |Cite
|
Sign up to set email alerts
|

Acute Tryptophan Depletion Effects on the Vertex and Late Positive Potentials to Emotional Faces in Individuals with a Family History of Depression

Abstract: Background: Depression, which is associated with dysfunctional serotonin (5-HT) activity, may be characterized by impaired emotional information processing. This study assessed the effects of acute tryptophan depletion (TRP–), which transiently lowers CNS 5-HT, on the emotion-sensitive vertex positive potential (VPP) and late positive potential (LPP) event-related potentials (ERPs) and mood in individuals with a family history of depression. The VPP and LPP are thought to index the early and later stages of mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 174 publications
2
9
0
Order By: Relevance
“…However, we previously found it to be enhanced to emotive (happy and sad) faces (Jaworska et al, 2011), consistent with the current study. Previous work has also found the VPP to be shortest to positive expressions (Batty & Taylor, 2003; Jaworska et al, 2011). Thus, highly arousing and positive faces appear to elicit maximal VPPs with shortest latencies.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…However, we previously found it to be enhanced to emotive (happy and sad) faces (Jaworska et al, 2011), consistent with the current study. Previous work has also found the VPP to be shortest to positive expressions (Batty & Taylor, 2003; Jaworska et al, 2011). Thus, highly arousing and positive faces appear to elicit maximal VPPs with shortest latencies.…”
Section: Discussionsupporting
confidence: 92%
“…For instance, increased emotive intensities (Sprengelmeyer & Jentzsch, 2006) and expressions of anger and fear enhanced the N170 (Batty & Taylor, 2003; Stekelenburg & de Gelder, 2004; Krombholz et al, 2007), though previous work from our group found it to be increased to joyful versus neutral and sad faces (Jaworksa et al, 2010). Similarly, the anterior face-sensitive vertex positive potential (VPP) has been shown to be more pronounced to negative versus neutral expressions (Sewell et al, 2008; Foti et al, 2010; Luo et al, 2010), though we found it to be enhanced to emotive (happy and sad) faces (Jaworska et al, 2011). Both N170 and VPP latencies were decreased to positive expressions (Batty & Taylor, 2003; Jaworska et al, 2011).…”
Section: Introductionmentioning
confidence: 51%
See 2 more Smart Citations
“…Both exaggerated and attenuated responses to emotional stimuli have been documented in generalized anxiety disorder (Weinberg & Hajcak, 2011), depression (Jaworska et al, 2012) and stress conditions (Weymar, Schwabe, Löw, & Hamm, 2012). Modulations in prefrontal regulation of emotional processing have been associated with aggressive and violent behaviour (Calzada-Reyes, Alvarez-Amador, Galán-García, & Valdés-Sosa, 2013; Reyes & Amador, 2009;Taft et al, 2007).…”
Section: The Lpp Componentmentioning
confidence: 99%